Fine-scale movement response of juvenile brown trout to hydropeaking - Robert Naudascher; Robert M. Boes; Vicente Fernandez; Joël Wittmann; Markus Holzner; Davide Vanzo; Luiz G.M. Silva; Roman Stocker (Science of The Total Environment, 2024)

Cutting Through the Noise: Bacterial Chemotaxis in Marine Microenvironments - Douglas R. Brumley; Francesco Carrara; Andrew M. Hein; George I. Hagstrom; Simon A. Levin; Roman Stocker (Frontiers in Marine Science, 2020)

Visualization of coral host–pathogen interactions using a stable GFP-labeled Vibrio coralliilyticus strain - F. Joseph Pollock; Cory J. Krediet; Melissa Garren; Roman Stocker; Karina Winn; Bryan Wilson; Carla Huete-Stauffer; Bette L. Willis; David G. Bourne (Coral Reefs, 2015)

Production and Bioactivity of Common Lichen Metabolites as Exemplified by Heterodea muelleri (Hampe) Nyl. - Armin Hager; Georg Brunauer; Roman Türk; Elfie Stocker-Wörgötter (Journal of Chemical Ecology, 2008)

Horizontal transport and dispersion in the surface layer of a medium‐sized lake - Roman Stocker; Jörg Imberger (Limnology and Oceanography, 2003)
Lagrangian GPS drifter experiments, carried out in the surface layer of stratified Lake Kinneret (Israel), are presented. Differential kinematic properties and Lagrangian statistics were calculated and used to estimate the dominant mechanisms for horizontal dispersion. On time scales smaller than a few internal wave periods, internal waves lead to strong divergence and convergence events, causing instantaneous apparent horizontal growth rates that were larger, by up to an order of magnitude, than the actual mean dispersion coefficient. It is shown that the internal wave field modulated the vorticity field so as to satisfy conservation of potential vorticity. On time scales larger than a few internal wave periods, unbounded horizontal shear dispersion was of the same order as the actual mean observed dispersion coefficient (K xy = 17.1 m 2 s −1 ), while vertical shear dispersion was negligible.

Modeling circulation in lakes: Spatial and temporal variations - Bernard Laval; Jörg Imberger; Ben R. Hodges; Roman Stocker (Limnology and Oceanography, 2003)
The influence of spatial and temporal variations in wind forcing on the circulation in lakes is investigated using field data and the three‐dimensional Estuary and Lake Computer Model (ELCOM) applied to Lake Kinneret. Lake Kinneret field data from six thermistor chains and eight wind anemometers deployed during July 2001 are presented. Internal wave motions are well reproduced by the numerical model when forced with a spatially uniform wind taken from a station near the lake center; however, simulated seiche amplitudes are too large (especially vertical mode 2) and lead observations by 3–10 h (for a 24‐h period wave) at different locations around the lake. Consideration of the spatial variation of the wind field improves simulated wave amplitude, and phase error at all stations is reduced to less than 1.5 h. This improvement is attributable to a better representation of the horizontally averaged wind stress and can be reproduced with a spatially uniform wind that has the same horizontally averaged wind stress as the spatially varying wind field. However, a spatially varying wind field is essential for simulating mean surface circulation, which is shown to be predominantly directly forced by the surface‐layer‐averaged wind stress moment.